Game on: Exploring constructive design behaviors through the use of real-time virtual engines in architectural education. (September 2016) - Moleta, TJ
Real-time virtual engines have experienced a degree of popularity in contemporary architectural education. Acknowledging that primarily the real-time virtual engine is deployed as a visualization tool, this article notes that the capacity to extend beyond the sensation of experiencing form and space exists through the deployment of the game mechanics. A survey of architecture students in digital design courses is used as a case study to identify how game mechanics can be used effectively in a design studio setting. The discussion concludes on the game mechanic as an opportunity to rescript design studio behaviors.